Larvicidal Activity of essential oils from Brazilian plants against Aedes aegypti L. - Eveline Solon Barreira Cavalcanti; Selene Maia de Morais; Michele Ashley A Lima; Eddie William Pinho Santana (Memorias do Instituto Oswaldo Cruz, 2004)
Aedes aegypti L. is the major vector of dengue fever, an endemic disease in Brazil. In an effort to find effective and affordable ways to control this mosquito, the larvicidal activities of essential oils from nine plants widely found in the Northeast of Brazil were analyzed by measurement of their LC50. The essential oils were extracted by steam distillation and their chemical composition determined by GL-chromatography coupled to mass spectroscopy. The essential oils from Cymbopogon citratus and Lippia sidoides, reported in the literature to have larvicidal properties against A. aegypti, were used for activity comparison. The results show that Ocimum americanum and Ocimum gratissimum have LC50 of 67 ppm and 60 ppm respectively, compared to 63 ppm for L. sidoides and 69 ppm for C. citratus. These results suggest a potential utilization of the essential oil of these two Ocimum species for the control of A. aegypti.